Influência de teores de impurezas no monitoramento de variáveis indiretas para detecção precoce da qualidade de soja armazenada em silos protótipos verticais - Dubal, Ítala Thaísa Padilha (2021)
Soybean (Glycine max L.) is an oilseed rich in proteins, fibers, vitamins and minerals, with high added value in the industry, essential for human and animal nutrition. Cleaning the grains after harvest is not always efficient, and residues and impurities are completely removed, which can intensify the respiration of the grain mass during storage. Thus, the objective of the study was to monitor the storage ecosystem and evaluate the influence of impurities in the grain mass in the early detection of the quality of soybeans stored in vertical silos over time. The work consisted of two experimental stages. In the first step, the impurities from the pre-cleaning machine were quantified to assess nutritional potential, in addition to evaluating the physicochemical quality in the processing and storage of soybeans. The second experimental stage was characterized by the monitoring of CO2 in metallic prototype silos. The temperature of the intergranular air, the temperature of the ambient air, the relative humidity of the ambient air and the relative humidity of the intergranular air were monitored. The hygroscopic equilibrium moisture was calculated and the dry matter loss of the stored grain mass through respiration in the grain mass was determined. Physiological, physical, physicalchemical, instrumental, mycotoxin and image quality analyzes were performed through laboratory tests. The results obtained in the first experimental stage showed that soybean by-products have nutritional value and can be used for food. In the second stage of the research, variations in temperature and relative humidity of the ambient air were observed, which influenced the conditions of the intergranular air and the increase in the respiratory rate of the mass of stored soybeans. The CO2 concentration varied in the three silos along the storage time, in Silo 1 it varied from 600 to 800 ppm, while in Silo 2 the CO2 concentration remained close to 400 ppm until the four months of storage. For silo 3, the values were higher and reached 5000 ppm in the third month of evaluation. The water contents of the stored grains reduced along the storage time with the increase in the temperature of the intergranular air. In general, the physical and physical-chemical quality analyzes obtained similar behavior of the materials stored in prototypes 1 and 2. Soybean grains stored in Silo 1 showed lower germination and electrical conductivity values. Storage time was the factor that had the greatest influence on the physical, physiological and physicochemical quality of soybeans. The monitoring of temperature and intergranular relative humidity, as well as the determination of the hygroscopic equilibrium humidity and the measurement of the concentration of CO2 indirectly predicted the physical, physiological and physicochemical changes in soybean quality during storage, being important input variables for early detection of soybean quality throughout storage.